The advertisement call of the poorly known Leptodactylus tapiti (Anura, Leptodactylidae) - Brandão, Reuber Albuquerque; Álvares, Guilherme Fajardo Roldão; de Sá, Rafael Omar (Zootaxa, 2013)
The genus Leptodactylus consists of approximately 80 species distributed in four nominal groups (Frost 2011). The fuscus group harbors approximately 30 small species with terrestrial nests, deposited in male built burrows on soft soils. Leptodactylus tapiti Sazima & Bokermann 1978 was described from Veadeiros, currently Alto Paraíso municipality,Goiás State,Brazil. The species is restricted to the region of Chapada dos Veadeiros (Frost 2011), where it occurs in areas of water-saturated soils associated with open fields (Sazima & Bokermann 1978). Since its original description, nothing was published about the species, and its advertisement call remains unknown. Herein, we describe its advertisement call.